ANALISIS ANGGARAN BIAYA SEBAGAI ALAT PENGENDALIAN BIAYA PRODUKSI PADA PROYEK PEMBANGUNAN TOWER TELEKOMUNIKASI DI LOMBOK - Ni Nyoman Yuliati Yuli; Nabila Ambarvia Putri; Endang Kartini (LPPM Universitas Gunung Rinjani, 2020)
This study intended to find the cause of the production cost variance in the project built by the Wino Tower and to find out whether the cost variance that occurs is included in the Favorable or Unfavorable difference. The research population is all telecommunication tower projects built by Wino Tower in 2016-2018 in Lombok. Samples were taken using purposive sampling. The criteria determined are telecommunication towers built by Wino Tower in 2016-2018 in Lombok with the same height of 50 meters and are still active right now. The analysis technique used in this study is analysis of variance. The results of this study indicate that the causal factor for the cost variance is because there is a variance in the cost of material price is Rp. 8,902,700 (2016), Rp. 4,878,225 (2017) and Rp. 2,647,700 (2018), the variance of cost of material quantity is Rp. 112,000 (2016), Rp. 420,000 (2017) and Rp. 1,150,000 (2018), and BOP controlled variance is Rp. 1,025,000 (2016), Rp. 1,520,000 (2017), and Rp. 1,250,000 (2018) that occurred. The results of this study also show that the variance in costs that occur in cost of materials and factory overhead costs is an unfavorable variance, while labor costs do not occur in the cost variance.